English Pronunciation Problems and Orthography Irregularities: Teacher Perspective Assessment in Sudanese Secondary School Context - Ali, Ezzeldin M.T.; Alsuni, Kawthar M. (CV Insan Kreasi Media, 2024)
Assessment of students from language teachers’ side represents one of the effective ongoing pedagogical activities that work to improve feedback about the performance of students. This study aims to measure the teachers' impressions about the pronunciation errors taking place due to the irregularities in English spelling. The teacher questionnaire provides data about students’ knowledge regarding the complex letter-to-sound relationships, teaching techniques, course content, and phonological awareness. The results revealed that the Sudanese learners have little knowledge about the relationship between letters and sounds and do not understand this connection, where the content of the English textbook does not address the pronunciation issue sufficiently. Moreover, teachers rarely provide learners with sufficient pronunciation practice activities that help them in decoding English letters to their sounds. Teachers are not satisfied with the content of the course and the narrow space given to the teaching of the link between letters and sounds. Finally, the students’ knowledge, teaching issues, and phonological awareness are dynamic factors in reducing the pronunciation errors due to irregularities of English spelling according to the teacher's point of view. Syllabus design should consider authentic and more advanced tactics for teaching English pronunciation in the EFL classroom. Key words: irregularities, content, phonological awareness letter to sound link, assessment